Pengaruh Model Pembelajaran Think Pair Share dan Problem Based Learning Terhadap Kemampuan Berpikir Kritis dan Pemecahan Masalah Siswa Kelas XI di SMAN 2 Sijunjung - Mona Amelia; Fatia Fatimah; Mery Noviyanti (Publikasi Indonesia, 2025)
This study examines the effectiveness of the Think Pair Share (TPS) and Problem Based Learning (PBL) models in improving students’ critical thinking and mathematical problem-solving abilities in Grade XI at SMAN 2 Sijunjung. The research was motivated by the gap between students’ learning interest and higher-order cognitive performance in probability material. A quantitative quasi-experimental design with a 2×2 factorial structure was employed, involving two equivalent classes (XI F-4 = TPS; XI F-5 = PBL; total n = 64). Data were collected through four-item essay tests based on Facione’s indicators of critical thinking and Polya’s steps of problem solving. Instrument validity, reliability, difficulty, and discrimination indices were verified before administration. The findings revealed that TPS outperformed PBL in both critical thinking (mean = 85.06 vs 80.00; F = 18.240; p < 0.05) and problem-solving skills (mean = 82.46 vs 77.63; F = 15.689; p < 0.05). Within-model comparisons also showed higher critical-thinking scores than problem-solving ones in both groups. These results confirm that TPS effectively fosters reasoning, argumentation, and structured analytical processes within limited instructional time, while PBL is better suited for long-term contextual application. The study concludes that structured social interaction significantly contributes to the development of higher-order thinking skills, and future research should explore retention effects and the sequential integration of TPS → PBL models.